Novel insights into pathophysiology, diagnostics and treatment of myelodysplastic syndromes - Haas, R. (Rainer), 1955-; Germing, Ulrich (Future Medicine Ltd (Unitec House, 2 Albert Place, London N3 1QB, UK), 2014)
This book aims to present, summarize and discuss the pathophysiological concept, diagnostic procedures and therapeutic approaches.